CARICOM, the CSME, and absolute sovereignty: lessons learnt on the road towards regional integration. Issue 1 (2nd January 2018) - Elias-Roberts, Alicia; Hanoman, Rocky R.
Abstract : As a regional bloc, the Revised Treaty of Chaguaramas (RTC) provides an opportunity for all of its Member States to benefit from regional integration and to better withstand the effects of globalisation. This article examines two recent cases involving Guyana that were litigated before the Caribbean Court of Justice (CCJ) (the 2009 "TCL Case" and 2014 "Rudisa Case") and discusses several important issues borne out during the cases, whereas also highlighting potential or emergent issues which may emanate from these cases in the future. These cases are analysed with a view to highlighting the important role of the CCJ in interpreting the RTC.